1971
DOI: 10.1152/ajplegacy.1971.221.4.980
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of insulin resistance in obese mice

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Mahler and Szabo [9] have shown that it is possible to get reversion of ob/ob characteristics by controlled treatment of suggest that the change in peripheral receptors could occur as a result of hyperinsulinaemia, reinforcing the previous suggestion that hypersecretion of insulin may be a primary fault. It has been shown that there is a close relationship between the functioning of e-and fl-cells in the islets [12].…”
Section: Abscissa ----Fraction Numbermentioning
confidence: 60%
“…Mahler and Szabo [9] have shown that it is possible to get reversion of ob/ob characteristics by controlled treatment of suggest that the change in peripheral receptors could occur as a result of hyperinsulinaemia, reinforcing the previous suggestion that hypersecretion of insulin may be a primary fault. It has been shown that there is a close relationship between the functioning of e-and fl-cells in the islets [12].…”
Section: Abscissa ----Fraction Numbermentioning
confidence: 60%
“…In the homozygous ob/ob mouse, marked islet cell hypertrophy in association with extremely high plasma insulin levels is seen with increasing adiposity while the blood sugar is normal and peripheral tissue responsivity to insulin is preserved and may, in fact, be increased (32,33). Suppression of pancreatic islet hyperplasia with alloxan restores the in vivo insulin sensitivity in the obese mice (40). Similarly, hyperinsulinemia has been demonstrated in the obese Zucker rat prior to the onset of peripheral insulin resistance (41).…”
Section: Resultsmentioning
confidence: 98%
“…Whereas many prior studies have established that insulin-stimulated glucose uptake or metabolism of muscle from the oblob mutation is decreased in vitro (31)(32)(33)(34)(35) Conditions were as described in Tables II, IV, and VI, except that 4% bovine albumin was used. [5-3H]glucose (sum of both glycogen synthesis and glycolysis), and decreased 2-deoxyglucose accumulation, all in the absence of insulin, and after two preincubations to remove whatever insulin might have been present in the tissue at death.…”
Section: Discussionmentioning
confidence: 99%